2018
DOI: 10.3390/ijms19020494
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Isoproterenol and Adenosine Treatment Confers Marked Protection against Reperfusion Injury in Adult but Not in Immature Heart: A Role for Glycogen

Abstract: Consecutive treatment of adult rat heart with isoproterenol and adenosine (Iso/Aden), known to consecutively activate PKA/PKC signaling, is cardioprotective against ischemia and reperfusion (I/R). Whether this is cardioprotective in an immature heart is unknown. Langendorff–perfused hearts from adult and immature (60 and 14 days old) male Wistar rats were exposed to 30 min ischemia and 120 min reperfusion, with or without prior perfusion with 5 nM Iso for 3 min followed by 30 μM Aden for 5 min. Changes in hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Ade and Iso, in addition to routine clinical use, also used to mimic the potent cardioprotection of temperature preconditioning by consecutive activation of protein kinases A and protein kinases C [10,11]. Moreover, Iso and Ade, alone or simultaneously, protected isolated rat hearts but the consecutive treatment gave the highest protection [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ade and Iso, in addition to routine clinical use, also used to mimic the potent cardioprotection of temperature preconditioning by consecutive activation of protein kinases A and protein kinases C [10,11]. Moreover, Iso and Ade, alone or simultaneously, protected isolated rat hearts but the consecutive treatment gave the highest protection [13].…”
Section: Discussionmentioning
confidence: 99%
“…Even so, our study had several limitations that should be considered. First of all, doses of Ade and Iso used in this study were selected according to our previous studies, without reference to those in vitro studies (sequentially with 5 nM Iso and 30 μM Ade) [10,11]. Further systematic exploration is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of either PKA or EPAC alone does not produce the same effect as with both; an intermediate response is seen. Our previous work [7,23] demonstrated that β-adrenoreceptor stimulation was in part responsible for a cardioprotective effect following a short period of activation. However, it is known that sustained activity at this receptor family does produce deleterious consequences for the heart at both the subcellular and whole organ level, including mitochondrial dysfunction, hypertrophy, heart failure, and death [24][25][26].…”
Section: Combined Stimulation Of Pka and Epac Provides Maximal Protection Against Injury In The Adult Heartmentioning
confidence: 99%
“…Norepinephrine as a humoral factor in RIP was first proposed by Dickson et al 18 Indeed, norepinephrine titers in the blood increase after RIP. 88 It should be noted that the stimulation of b-adrenergic receptors in the period preceding ischemia can promote an increase in cardiac tolerance to I/R, 89,90 so norepinephrine cannot be discounted as both a neurogenic and a humoral factor in RIP.…”
Section: Norepinephrinementioning
confidence: 99%